Intracapsular hip fracture and the region-specific loss of cortical bone: analysis by peripheral quantitative computed tomography. - Crabtree, N; Loveridge, N; Parker, M; Rushton, N; Power, J; Bell, K; Beck, T; Reeve, J (2001)
Generalized bone loss within the femoral neck accounts for only 15% of the increase in intracapsular hip fracture risk between the ages of 60 and 80 years. Conventional histology has shown that there is no difference in cancellous bone area between cases of intracapsular fracture and age and sex-matched controls. Rather, a loss of cortical bone thickness and increased porosity is the key feature with the greatest change occurring in those regions maximally loaded during a fall (the inferoanterior [IA] to superoposterior [SP] axis). We have now reexamined this finding using peripheral quantitative computed tomography (pQCT) to analyze cortical and cancellous bone areas, density, and mass in a different set of ex vivo biopsy specimens from cases of intracapsular hip fracture (female, n = 16, aged 69-92 years) and postmortem specimens (female, n = 15, aged 58-95 years; male, n = 11, aged 56-86 years). Within-neck location was standardized by using locations at which the ratio of maximum to minimum external diameters was 1.4 and at more proximal locations. Cortical widths were analyzed using 72 radial profiles from the center of area of each of the gray level images using a full-width/half-maximum algorithm. In both male and female controls, cancellous bone mass increased toward the femoral head and the rate of change was gender independent. Cancellous bone mass was similar in cases and controls at all locations. Overall, cortical bone mass was significantly lower in the fracture cases (by 25%; p < 0.001) because of significant reductions in both estimated cortical area and density. These differences persisted at locations that are more proximal. The mean cortical width in the cases was significantly lower in the IA (22.2%;p = 0.002) and inferior regions (19%;p < 0.001). The SP region was the thinnest in both cases and controls. These data confirm that a key feature in the etiology of intracapsular hip fracture is the site-specific loss of cortical bone, which is concentrated in those regions maximally loaded during a fall on the greater trochanter. An important implication of this work is that the pathogenesis of bone loss leading to hip fracture must be by a mechanism that varies in its effect according to location within the femoral neck Key candidate mechanisms would include those involving locally reduced mechanical loading. This study also suggests that the development of noninvasive methodologies for analyzing the thickness and estimated densities of critical cortical regions of the femoral neck could improve detection of those at risk of hip fracture.